Snow and Ice Control (SNIC) Equipment and Its Use by Military Units Worldwide - Collins, Nicholas H. (2002)
When the U.S. Army moved into Yugoslavia in December 1995, it did so without snow and ice control (SNIC) equipment. The only available tools-the bucket loader mounted on SEE tractors, scoop loaders, full-track tractors, the M9 ACE, and the motorized road grader-were not designed for SNIC. These tools are specialized and dedicated to specific missions, and attempts to use them for SNIC proved detrimental to both the equipment and the areas requiring snow removal. Upon receipt of an urgent call from HQUSACE, it was determined that a SEE tractor snowplow prototype had been designed by the manufacturer that built and produced the SEE's front loader bucket. Within six days, the company built a SEE snowplow and shipped it to Jericho, Vermont, where it was installed on a Vermont Army National Guard (ARNG) SEE tractor The snow- plow was tested in various scenarios, at various snow depths, at temperatures as low as -15 deg F. It performed better than expected and 17 SEE snowplows were sent to Task Force Eagle in Bosnia. Since then, snowplows for the 5-ton truck and HMMWV have been fielded to reduce the workload placed on the SEE tractor The viability of using this equipment on various snow-covered terrain by soldiers from the 10th Mountain Division (Light Infantry) at Fort Drum, New York, and the Ethan Allen Training Center in Vermont, was demonstrated. The original document contains color images.